Qualities transmitted by territorial branding. Proposal for a new typology - Champredonde, Marcelo (2016)
Abstract – Several ways exist for connecting food to place. From Geographical Indications (with a strong link) to umbrella branding (with weaker links), local actors have a large range of possibilities at their disposal. Territorial branding is very often used in Europe and in Latin America as well for identifying this connection. So, we are facing a great diversity of situations where some link is supposed to be present for justifying a geographical name associated to a food. We explore a new way to classify the foods concerned using some attributes (recent vs ancient activity) or properties (generic vs specific resources) allowing diverse qualifications for the foods. We discuss such classification according to the previous typologies available.